Transient neonatal myasthenia gravis: case report - Diana Iulia Vasilescu; Adriana Mihaela Dan; Vlad Dima; Monica Mihaela Cirstoiu (Romanian Medical Journal, 2022)
Transient neonatal myasthenia gravis (TNMG) is a distinct type of myasthenia gravis (MG), a temporary autoimmune condition due to the mother’s antibodies crossing over the placenta and affecting the baby. Studies suggest that 10 to 15% of infants born to mothers suffering from MG will develop TNMG. Undoubtedly, if not diagnosed and treated in time, TNMG can be a serious condition, even life-threatening. Almost 80% of newborns will present symptoms in the first 24 hours of life that will last up to 4 weeks and a complete recovery is expected by 2 months of age. Only 10% of the affected infants may still be symptomatic at 4 months.